Dataset for Cranfield University GBSAR Laboratory Data - Boat Model - Rattan, Anmol; Andre, Daniel (Cranfield University, 2026)
This dataset supports the study entitled “Multistatic Frequency- and Polarimetry-Adaptive Autofocus for SAR Imaging of a Moving Target”. The dataset contains multistatic fully polarimetric SAR phase-history measurements acquired using the Cranfield University Ground-Based SAR (GBSAR) laboratory system. Measurements include HH, HV, VH and VV polarisation channels collected over an X-band frequency range. The dataset is provided as a MATLAB structure array containing phase-history measurements, radar trajectory coordinates and associated sensor parameters used for SAR image formation via back-projection imaging. Included trajectories comprise both target motion-inverted SAR trajectories used to produce ideally focused SAR imagery and uncorrected trajectories corresponding to unfocused imagery. Supporting parameters include pulse counts, frequency sampling information, centre frequency and bandwidth.
Keywords: Multistatic; Bistatic; SAR; Radar; MATLAB